Anti-reflection PMMA optical material and manufacturing method thereof

By forming a nanoparticle anti-reflection layer with chemical bonding and surface contact on the surface of the PMMA matrix, the problem of difficulty in forming an anti-reflection layer with excellent mechanical properties and durable on the PMMA matrix is ​​solved, and efficient light transmission and cost reduction are achieved.

CN119708596APending Publication Date: 2025-03-28HAIYAN HUASHUAITE PLASTIC ELECTRICAL APPLIANCES CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411986900.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art is difficult to form an anti-reflective layer with excellent mechanical properties and durable mechanical properties on the PMMA substrate, and the cost is high.

Method used

By infiltrating the dispersion of nanoparticles on the surface of the PMMA matrix and controlling the ambient temperature and negative pressure conditions in a constant temperature box, the MMA monomer and the photoinitiator are vaporized to form an anti-reflective layer that is chemically bonded and surface-contact.

Benefits of technology

The formation of an anti-reflective layer with excellent mechanical properties and durable mechanical properties on the PMMA substrate is achieved, which improves light transmission performance and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708596A_ABST
    Figure CN119708596A_ABST
Patent Text Reader

Abstract

The invention relates to an anti-reflection PMMA optical material and a manufacturing method thereof. The method comprises the steps that the surface of a PMMA matrix with the surface containing a first functional group is infiltrated with dispersion liquid of nanoparticles with the surface containing a second functional group; putting the modified PMMA matrix into a constant temperature box, controlling a temperature environment and a negative pressure condition, sequentially providing a gas atmosphere consisting of an MMA monomer and a photoinitiator, a gas atmosphere of a chemical substance chemically bonded with a first functional group and a second functional group, and a gas atmosphere consisting of the MMA monomer and the photoinitiator, and finally carrying out irradiation treatment to obtain the light-cured PMMA matrix. And carrying out polymerization reaction on the MMA monomer to obtain the anti-reflection PMMA optical material. According to the technical scheme, by providing different gas atmospheres and providing the sequence of the different gas atmospheres, chemical bonding and surface contact can be formed between the nanoparticles and the PMMA substrate, the reliability of the antireflection layer is improved, and the antireflection layer is low in cost, excellent in mechanical performance and durable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of optical materials, and in particular to an anti-reflective PMMA optical material and a method for manufacturing the same. Background Art

[0002] Anti-reflection layers are widely used in the optical field due to their technical characteristics of reducing reflection loss and increasing light transmittance, including architectural glass, photovoltaic modules, displays, optical lenses and eyeglasses. There are many ways to form anti-reflection layers, such as using electrochemical etching technology to achieve zero reflection in the blue band on a silicon substrate; or using nanoimprint lithography to obtain an anti-reflection layer with excellent mechanical properties and durability on a glass substrate. However, these technologies not only require the regulation of precise mask patterns, but also are accompanied by complex processing procedures. In addition, various physical sputtering processes are also used to manufacture anti-reflection layers, but the process is time-consuming, and the expensive vacuum system also requires high capital and maintenance costs.

[0003] Compared with traditional inorganic glass, polymethyl methacrylate (PMMA) has more significant advantages, such as optical transparency, low manufacturing energy consumption and low density, and also has higher impact resistance, making it an ideal material for the anti-reflection layer matrix. How to form an anti-reflection layer on a PMMA matrix to reduce reflection loss, reduce costs and obtain optical materials with excellent mechanical properties and durability still needs to be broken through. Summary of the invention

[0004] In response to the above technical problems, the present application provides an anti-reflection PMMA optical material and a method for manufacturing the same, which can form an anti-reflection layer with excellent mechanical properties and durability on a PMMA substrate, thereby improving light transmittance and having low cost.

[0005] In order to solve the above technical problems, the present application provides an anti-reflection PMMA optical material, including a PMMA substrate and an anti-reflection layer formed on at least a portion of the surface of the PMMA substrate, wherein the anti-reflection layer is composed of nanoparticles, and chemical bonds are formed between the nanoparticles and the PMMA substrate, and at least a portion of the nanoparticles are embedded in the surface of the PMMA substrate to form surface contact.

[0006] The present application also provides a method for manufacturing an anti-reflection PMMA optical material, comprising the following steps: S1, providing a PMMA substrate having a first functional group on the surface, and providing a dispersion of nanoparticles having a second functional group on the surface; S2, infiltrating the dispersion of the nanoparticles on at least a portion of the surface of the PMMA substrate, and drying, to obtain a first modified substrate; S3, placing the first modified substrate and a container containing a homogeneous solution composed of MMA monomer and photoinitiator in a constant temperature box, controlling the ambient temperature and negative pressure conditions, so that the MMA monomer and the photoinitiator are vaporized and deposited on the surface of the first modified substrate, dissolving and softening the surface of the first modified substrate, so that the nanoparticles are embedded in the surface of the first modified substrate to form surface contact, and obtaining a second modified substrate; S4, placing the second modified matrix and a container containing a chemical substance for chemically bonding with the first functional group and the second functional group in a constant temperature box, controlling the ambient temperature and negative pressure conditions, and vaporizing the chemical substance to infiltrate the surface of the nanoparticle and enter the surface contact area along the curved surface of the nanoparticle, forming a chemical bond between the nanoparticle and the second modified matrix in the surface contact area, and obtaining a third modified matrix; S5, placing the third modified substrate and a container containing a homogeneous solution composed of MMA monomer and photoinitiator in a constant temperature box, controlling the ambient temperature and negative pressure conditions, so that the MMA monomer and the photoinitiator are vaporized and deposited on the surface of the third modified substrate, dissolving and softening the surface of the third modified substrate and filling the surface contact area; S6, performing irradiation treatment to cause the MMA monomer to undergo a polymerization reaction, thereby obtaining an anti-reflective PMMA optical material.

[0007] In some embodiments, providing a PMMA substrate having a first functional group on its surface comprises: Providing a liquid matrix material, the liquid matrix material comprising a prepolymerized liquid formed by bulk polymerization of MMA, an unsaturated monomer containing the first functional group, the chemically bonded reaction catalyst and a thermal initiator; A polymerization reaction is carried out to make the liquid matrix material form a solid matrix, thereby obtaining a PMMA matrix having a first functional group on the surface.

[0008] In some embodiments, in the liquid matrix material, the mass ratio of the prepolymer liquid, the unsaturated monomer containing the first functional group, and the chemically bonded reaction catalyst is (60 ~ 90): (5 ~ 20): (0.2 ~ 2), and the mass proportion of the thermal initiator in the liquid matrix material is ≤0.8%.

[0009] In some embodiments, the first functional group and the second functional group are both hydroxyl groups, and the chemical substance is diisocyanate; The first functional group is a primary amino group or a secondary amino group, the second functional group is a hydroxyl group, and the chemical substance is a first silane coupling agent; The first functional group is an epoxy group, the second functional group is a hydroxyl group, and the chemical substance is a second silane coupling agent.

[0010] In some embodiments, the particle size of the nanoparticles is less than 380 nm, and the type of the nanoparticles includes at least one of silicon dioxide and titanium dioxide.

[0011] In some embodiments, the second functional group is a hydroxyl group, and providing a dispersion of nanoparticles having the second functional group on the surface includes: Under room temperature, a mixture consisting of ethanol, tetraethyl silicate or tetraethyl titanate, and ammonia water is prepared; After stirring for a certain period of time, the mixture is sealed with a light-shielding material and allowed to stand for aging to form a dispersion of nanoparticles having a second functional group on the surface.

[0012] In some embodiments, before S3, the method further includes: The first modified substrate and a container containing ammonia water are placed in a constant temperature box, and the ambient temperature and negative pressure conditions are controlled to vaporize the ammonia water to obtain ammonia gas, which has a hardening effect on the anti-reflection layer composed of the nanoparticles.

[0013] In some embodiments, at least one of the following is included: In S3, the negative pressure state lasts for 30 to 60 minutes at 25 to 50 °C, and the product is dried by air blast after the pressure is released; In S4, the negative pressure state lasts for 30 to 60 minutes at 25 to 50 °C, and the product is dried by air blast after the pressure is released; In S5, the negative pressure state lasts for 30 to 60 min at 25 to 50 °C.

[0014] In some embodiments, the S2 includes: Immersing at least a portion of the surface of the PMMA substrate into the dispersion of the nanoparticles for a time greater than or equal to 30 s; Pulling into the air in a vertical or oblique direction, with a pulling speed less than or equal to 1 mm / s; The mixture was dried by natural evaporation to obtain a first modified matrix.

[0015] The present application also provides an anti-reflection PMMA optical material, which is manufactured using the above-mentioned method for manufacturing the anti-reflection PMMA optical material.

[0016] The present application provides an anti-reflection PMMA optical material, comprising a PMMA substrate and an anti-reflection layer formed on at least a portion of the surface of the PMMA substrate, wherein the anti-reflection layer is composed of nanoparticles, chemical bonding is formed between the nanoparticles and the PMMA substrate, and at least a portion of the nanoparticles are embedded in the surface of the PMMA substrate to form a surface contact. The technical solution of the present application forms a chemical bond and a surface contact between the nanoparticles and the PMMA substrate, thereby improving the reliability of the anti-reflection layer, which not only has excellent mechanical properties, but is also more durable.

[0017] The present application relates to an anti-reflection PMMA optical material and a manufacturing method thereof, the method comprising: infiltrating a dispersion of nanoparticles having a second functional group on the surface of a PMMA substrate having a first functional group on the surface; placing the modified PMMA substrate in a constant temperature box, controlling the temperature environment and negative pressure conditions, sequentially providing a gas atmosphere composed of an MMA monomer and a photoinitiator, a gas atmosphere of a chemical substance for chemically bonding with the first functional group and the second functional group, and a gas atmosphere composed of an MMA monomer and a photoinitiator, and finally performing irradiation treatment to polymerize the MMA monomer to obtain an anti-reflection PMMA optical material. The technical solution of the present application, by providing different gas atmospheres and providing different gas atmospheres in sequence, can form chemical bonding and surface contact between the nanoparticles and the PMMA substrate, thereby improving the reliability of the anti-reflection layer, which is not only low in cost, but also has excellent mechanical properties and is durable. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a schematic structural diagram of an anti-reflection PMMA optical material in this application.

[0019] Figure 2 It is a schematic diagram of a process for manufacturing an anti-reflective PMMA optical material in the present application.

[0020] Figure 3 It is a schematic diagram of the principle of a method for manufacturing an anti-reflective PMMA optical material in this application.

[0021] Figure 4 These are the static water contact angle test results of Examples 1 to 3 and Control Groups 1 to 2 in this application.

[0022] Figure 5 It is a combination of freeze-frame images of the video shot at corresponding times during the static water contact angle test process of Examples 1 to 3 and Control Groups 1 to 2 in the present application.

[0023] Figure 6 Schematic diagram of UV-Vis spectrum characterization results of control groups 1 to 2 and examples 1 to 3 in the present application.

[0024] Figure 7These are the field emission scanning electron microscopy characterization results at different magnifications of Example 3 in the present application.

[0025] Figure 8 This is the atomic force microscopy characterization result of Example 3 in this application. DETAILED DESCRIPTION

[0026] The following is an explanation of the implementation of the present application by means of specific embodiments. People familiar with the art can easily understand other advantages and effects of the present application from the contents disclosed in this specification.

[0027] In the following description, reference is made to the accompanying drawings, which describe several embodiments of the present application. It should be understood that other embodiments may be used and that mechanical, structural, electrical, and operational changes may be made without departing from the spirit and scope of the present application. The following detailed description should not be considered limiting, and the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present application.

[0028] Although the terms first, second, etc. are used herein to describe various elements in some instances, these elements should not be limited by these terms. These terms are only used to distinguish one element from another element.

[0029] Furthermore, as used in this article, the singular forms "one", "an" and "the" are intended to include plural forms as well, unless there is an indication to the contrary in the context. It should be further understood that the terms "comprise", "include" indicate the presence of the described features, steps, operations, elements, components, projects, kinds, and / or groups, but do not exclude the presence, occurrence or addition of one or more other features, steps, operations, elements, components, projects, kinds, and / or groups. The terms "or" and "and / or" used herein are interpreted as inclusive, or mean any one or any combination. Therefore, "A, B or C" or "A, B and / or C" means "any of the following: A; B; C; A and B; A and C; B and C; A, B and C". Exceptions to this definition will only occur when the combination of elements, functions, steps or operations is inherently mutually exclusive in some way.

[0030] First embodiment Figure 1 Schematic diagram of the structure of an anti-reflective PMMA optical material in this application. Figure 1 As shown, the present application provides an anti-reflection PMMA optical material, including a PMMA substrate 10 and an anti-reflection layer 20 formed on at least a portion of the surface of the PMMA substrate 10, the anti-reflection layer 20 is composed of nanoparticles 21, chemical bonds are formed between the nanoparticles 21 and the PMMA substrate 10, and at least a portion of the nanoparticles 21 are embedded in the surface of the PMMA substrate 10 to form surface contact.

[0031] The nanoparticles 21 are embedded in the surface of the PMMA matrix 10, which specifically means that the height of the nanoparticles 21 on the surface of the PMMA matrix 10 is less than the outer diameter of the nanoparticles 21, but greater than 1 / 2 of the outer diameter of the nanoparticles 21. Therefore, the interaction between the nanoparticles 21 and the PMMA matrix 10 involves the synergy of multiple factors including physical embedding, chemical bonding, and surface contact, and the two form a robust "integrated" feature.

[0032] In some embodiments, the particle size of the nanoparticles 21 is less than 380 nm, and the type of the nanoparticles 21 includes at least one of silicon dioxide and titanium dioxide.

[0033] In some embodiments, the nanoparticles 21 are prepared by a sol-gel process and hardened by ammonia.

[0034] In some embodiments, the chemical bonding is formed by addition reaction of hydroxyl groups or carboxyl groups on the surface of the PMMA matrix 10 and hydroxyl groups on the surface of the nanoparticles 21 with diisocyanate, respectively.

[0035] In some embodiments, the chemical bonding may also be formed by addition reactions of the primary amino group or secondary amino group on the surface of the PMMA matrix 10 and the hydroxyl group on the surface of the nanoparticles 21 with the first silane coupling agent.

[0036] In some embodiments, the chemical bonding may also be formed by addition reaction of the epoxy groups on the surface of the PMMA matrix 10 and the hydroxyl groups on the surface of the nanoparticles 21 with the second silane coupling agent.

[0037] The above chemical bonding ultimately forms substantially the same bonding force in the surface contact area between the nanoparticles 21 and the PMMA matrix 10 .

[0038] In some embodiments, the diisocyanate includes at least one of p-phenylene diisocyanate, m-phenylenediisocyanate, 1,3-phenylene diisocyanate, toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, cyclohexane-1,4-diisocyanate, hexamethylene diisocyanate, toluene 2,5-diisocyanate, 2,2'-methylene diphenyl diisocyanate, trans-1,4-cyclohexane diisocyanate, isophorone diisocyanate, trimethylhexamethylene diisocyanate, dicyclohexylmethane 4,4'-diisocyanate, 1,4-butyl diisocyanate, and 1,5-naphthalene diisocyanate.

[0039] In some embodiments, the first silane coupling agent is a silane coupling agent with epoxy and siloxane as terminal groups, specifically including at least one of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane, 3-[(2,3)-epoxypropyloxy]propylethyldiethoxysilane, triethoxy(3-epoxypropyloxypropyl)silane, and trimethoxy(3-epoxypropyloxypropyl)silane.

[0040] In some embodiments, the second silane coupling agent is a silane coupling agent with amino and siloxane as terminal groups, specifically including at least one of trimethoxy [3- (phenylamino) propyl] silane, trimethoxy [3- (methylamino) propyl] silane, triethoxy [3- (phenylamino) propyl] silane, triethoxy [3- (methylamino) propyl] silane, (3-aminopropyl) dimethylmethoxy silane, 3- [2- (2-aminoethylamino) ethylamino] propyl-trimethoxy silane, 3-aminopropyl triethoxy silane, [3- (6-aminohexylamino) propyl] trimethoxy silane, and aminoethylaminoisobutylmethyldimethoxy silane.

[0041] The present application provides an anti-reflection PMMA optical material, comprising a PMMA substrate and an anti-reflection layer formed on at least a portion of the surface of the PMMA substrate, wherein the anti-reflection layer is composed of nanoparticles, chemical bonding is formed between the nanoparticles and the PMMA substrate, and at least a portion of the nanoparticles are embedded in the surface of the PMMA substrate to form a surface contact. The technical solution of the present application forms a chemical bond and a surface contact between the nanoparticles and the PMMA substrate, thereby improving the reliability of the anti-reflection layer, which not only has excellent mechanical properties, but is also more durable.

[0042] Figure 2 FIG. 1 is a flow chart of a method for manufacturing an anti-reflective PMMA optical material in the present application. Figure 2 As shown, a method for manufacturing an anti-reflection PMMA optical material of the present application comprises the following steps: S1, providing a PMMA substrate having a first functional group on the surface, and providing a dispersion of nanoparticles having a second functional group on the surface; S2, infiltrating at least a portion of the surface of the PMMA substrate with a dispersion of nanoparticles, and drying the dispersion to obtain a first modified substrate; S3, placing the first modified substrate and a container containing a homogeneous solution composed of MMA monomer and photoinitiator in a constant temperature box, controlling the ambient temperature and negative pressure conditions, so that the MMA monomer and the photoinitiator are vaporized and deposited on the surface of the first modified substrate, dissolving and softening the surface of the first modified substrate, so that the nanoparticles are embedded in the surface of the first modified substrate to form surface contact, and obtaining a second modified substrate; S4, placing the second modified substrate and a container containing a chemical substance for chemically bonding with the first functional group and the second functional group in a constant temperature box, controlling the ambient temperature and negative pressure conditions, vaporizing the chemical substance to infiltrate the surface of the nanoparticles and enter the surface contact area along the curved surface of the nanoparticles, forming a chemical bond between the nanoparticles and the second modified substrate in the surface contact area, and obtaining a third modified substrate; S5, placing the third modified substrate and a container containing a homogeneous solution composed of MMA monomer and photoinitiator in a constant temperature box, controlling the ambient temperature and negative pressure conditions, so that the MMA monomer and the photoinitiator are vaporized and deposited on the surface of the third modified substrate, dissolving and softening the surface of the third modified substrate and filling the surface contact area; S6, performing irradiation treatment to cause polymerization reaction of the MMA monomer to obtain an anti-reflective PMMA optical material.

[0043] Through the above process, based on step S3 to step S5, after the modified PMMA substrate is placed in a constant temperature box, the temperature environment and negative pressure conditions are controlled to sequentially provide a gas atmosphere composed of MMA monomers and photoinitiators, a gas atmosphere of chemical substances for chemically bonding with the first functional group and the second functional group, and a gas atmosphere composed of MMA monomers and photoinitiators. In this process, the process of embedding nanoparticles into the surface of the first modified substrate to form surface contact, forming chemical bonds between the nanoparticles and the second modified substrate in the surface contact area, and wetting the surface contact area by MMA monomers and photoinitiators is sequentially completed. Finally, irradiation treatment is performed to cause a polymerization reaction of the MMA monomer, so that the final interaction mode between the nanoparticles and the PMMA substrate has a multi-factor synergy of physical embedding, chemical bonding, and surface contact, and the two form a robust "integrated" feature, thereby obtaining an anti-reflective PMMA optical material.

[0044] It can be seen that in the manufacturing process, there is no need to use sophisticated and complex equipment. The strong adhesion between the nanoparticles and the substrate is guaranteed by the reasonable setting of the process sequence of chemical bonding and physical embedding. While improving the reliability, mechanical properties and durability of the anti-reflection layer, the use of high-temperature treatment procedures is avoided, making it more suitable for PMMA substrates with a thermal deformation temperature of less than 120°C.

[0045] In some embodiments, in step S1, providing a PMMA substrate having a first functional group on its surface comprises: Providing a liquid matrix material, the liquid matrix material comprising a prepolymerized liquid formed by bulk polymerization of MMA, an unsaturated monomer containing a first functional group, a chemically bonded reaction catalyst and a thermal initiator; A polymerization reaction is carried out to make the liquid matrix material form a solid matrix, thereby obtaining a PMMA matrix having a first functional group on the surface.

[0046] The viscosity of the prepolymer solution is specifically 20 to 150 s for a 4-cup coating flow time at 25°C.

[0047] The first functional group can be selected as a hydroxyl group, and the hydroxyl-containing unsaturated monomer can be selected from at least one of hydroxypropyl methacrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxyethyl acrylate, 4-hydroxybutyl acrylate, 2,2-bis(allyloxymethyl)-1-butanol, methallyl alcohol, ethylene glycol monoallyl ether, 10-undecenol, 6-shogaol, curcumin, chlorogenic acid, caffeic acid, 4-coumaric acid, ferulic acid, sinapinic acid, 4-acetyl-2-allylphenol, 2-allylphenol, 4-hydroxystyrene, 4-isopropenylphenol, eugenol, 4-penten-1-ol, 3-butene-1-ol, 1-butene-3-ol, 4-penten-2-ol, cinnamyl alcohol, 3-allyloxy-1,2-propanediol, 3-methyl-2-butene-1-ol, 2-methyl-3-butene-2-ol, and 2-butene-1-ol.

[0048] The first functional group can be a carboxyl group, and the unsaturated monomer containing a carboxyl group can be selected from at least one of myristoleic acid, 11-hexadecenoic acid, 10-undecenoic acid, 11-dodecenoic acid, 2,4-pentadienoic acid, acrylic acid, methacrylic acid, 3-butenoic acid, 2-methyl-3-butenoic acid, 4-pentenoic acid, 3-pentenoic acid, 5-hexenoic acid, 4-methyl-3-hexenoic acid, 6-heptenoic acid, 3-heptenoic acid, and 7-octenoic acid.

[0049] The first functional group can also be selected from a primary amino group or a secondary amino group, and the unsaturated monomer containing a primary amino group or a secondary amino group can be selected from at least one of N-allyl-2-aminomethylpyrrolidine, 2-[2-(3-prop-1-en-2-ylphenyl)propane-2-ylcarbamoyloxy]ethyl methacrylate, 3-allylaminocarbonylphenylboric acid, N-methylallylamine, N-allyl-N-tert-butylamine, allylcyclohexylamine, 2-methylallylamine, N-allyl-N-isopropylamine, acrylamide, and methacrylamide.

[0050] The first functional group may also be an epoxy group, and the unsaturated monomer containing the epoxy group may be selected from at least one of allyl glycidyl ether, 4-hydroxybutyl acrylate glycidyl ether, and methacrylate glycidyl ether.

[0051] The catalyst functions to accelerate the chemical bonding reaction between the first functional group, the second functional group and the chemical substance. In some embodiments, the first functional group and the second functional group are both hydroxyl groups, the chemical substance is diisocyanate, and the catalyst is selected from at least one of dibutyltin dilaurate, dibutyltin diacetate, potassium neodecanoate, zinc neodecanoate, tetrabutyltin, dibutyldimethoxytin, monobutyltin triisooctanoate, trimethylamine, and triethylamine.

[0052] In some embodiments, the diisocyanate includes at least one of p-phenylene diisocyanate, m-phenylenediisocyanate, 1,3-phenylene diisocyanate, toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, cyclohexane-1,4-diisocyanate, hexamethylene diisocyanate, toluene 2,5-diisocyanate, 2,2'-methylene diphenyl diisocyanate, trans-1,4-cyclohexane diisocyanate, isophorone diisocyanate, trimethylhexamethylene diisocyanate, dicyclohexylmethane 4,4'-diisocyanate, 1,4-butyl diisocyanate, and 1,5-naphthalene diisocyanate.

[0053] The thermal initiator is used to realize the polymerization reaction of the liquid matrix material under thermal initiation to form a solid matrix, and is selected from at least one of BPO, AIBN, and ABVN.

[0054] In some embodiments, in the liquid matrix material, the mass ratio of the prepolymer liquid, the unsaturated monomer containing the first functional group, and the chemically bonded reaction catalyst is (60 ~ 90): (5 ~ 20): (0.2 ~ 2), and the mass proportion of the thermal initiator in the liquid matrix material is ≤0.8%.

[0055] The process of the polymerization reaction, when forming a substrate with a thickness of less than or equal to 10 mm, is specifically a water bath at 35-65°C for 2-12 hours, and a forced air bath at 105-135°C for 1-8 hours. When the thickness exceeds 10 mm, the specific water bath or air bath time should be adaptively extended according to actual conditions.

[0056] In some embodiments, the particle size of the nanoparticles is less than 380 nm, and the types of nanoparticles include at least one of silicon dioxide and titanium dioxide. Compared with other technologies for infiltrating a PMMA substrate to form a coating, the dispersion obtained by the sol-gel process has many advantages such as low temperature, convenient deposition, low cost, and controllable structure, and is more suitable for universal industrial applications. At the same time, the sol-gel process is suitable for preparing dispersions of silicon dioxide and / or titanium dioxide. It is understandable that the dispersion can also be obtained by re-dispersing the nanoparticles after the nanoparticles are prepared in advance.

[0057] In some embodiments, when the dispersion is obtained by a sol-gel process, the surface of the nanoparticles naturally contains abundant hydroxyl functional groups, and therefore, the second functional group is a hydroxyl group. In step S1, providing a dispersion of nanoparticles having the second functional group on the surface includes: Prepare a mixture consisting of ethanol, tetraethyl silicate or tetraethyl titanate, and aqueous ammonia; After stirring for a certain period of time, the mixture is sealed with a light-shielding material and allowed to stand for aging to form a dispersion of nanoparticles having a second functional group on the surface.

[0058] Among them, in the mixture composed of ethanol, tetraethyl silicate or tetraethyl titanate, and ammonia water, the mass ratio of ethanol, tetraethyl silicate or tetraethyl titanate, and ammonia water is (80 ~ 100): (5 ~ 15): (5 ~ 10). It is further explained that when the temperature under room temperature is greater than 25 ° C, the stirring and aging time can be appropriately shortened according to actual conditions.

[0059] In some embodiments, step S2 includes: Immersing at least a portion of the surface of the PMMA substrate in the dispersion of the nanoparticles for a time greater than or equal to 30 seconds; Pulling into the air in a vertical or oblique direction, with a pulling speed less than or equal to 1 mm / s; The mixture was dried by natural evaporation to obtain a first modified matrix.

[0060] Among them, there is no blasting during the heat preservation process after pulling, maintaining a natural thermal evaporation state, so that the nanoparticles have an ideal environment for adaptive arrangement. Please refer to Figure 3 After completing step S2, nanoparticles are distributed on at least a portion of the surface of the PMMA substrate.

[0061] When the nanoparticles are obtained by a sol-gel process, the texture of the nanoparticles tends to be soft. Therefore, in some embodiments, before step S3, the process further includes: S21, placing the first modified substrate and a container containing ammonia water in a constant temperature box, controlling the ambient temperature and negative pressure conditions, so that the ammonia water is vaporized to obtain ammonia gas, which has a hardening effect on the anti-reflection layer composed of nanoparticles.

[0062] Among them, at 45 ℃, negative pressure state for 2 to 5 hours can better form an ammonia atmosphere. Since ammonia exists in the ammonia water in the container, it has a low boiling point and is volatile, so a moderate thermal environment can allow ammonia to vaporize from the ammonia water. A moderate negative pressure can make it fill more inside the constant temperature box, and then deposit on the surface of the modified substrate at this time, hardening the anti-reflection layer composed of nanoparticles. A few hours of treatment time at 45 ℃ is enough to ensure a sufficient hardening effect. Please refer to Figure 3 After completing step S21, the surface of the nanoparticles is hardened, and the distribution of the nanoparticles on the surface of the PMMA substrate does not change significantly.

[0063] In some embodiments, at least one of the following is included: In S3, the negative pressure state lasts for 30 to 60 minutes at 25 to 50 °C, and the product is dried by air blast after the pressure is released; In S4, the negative pressure state lasts for 30 to 60 minutes at 25 to 50 °C, and the product is dried by air blast after the pressure is released; In S5, the negative pressure state lasts for 30 to 60 min at 25 to 50 °C.

[0064] Among them, under the selected temperature conditions, the liquid composition in the corresponding container can be vaporized and enter the constant temperature box, and the negative pressure environment can further accelerate the vaporization degree of the corresponding composition. The vacuum gauge value range of the negative pressure state is 0.05~0.1 MPa, that is, negative half an atmosphere to negative one atmosphere. It should be noted that the specific vacuum gauge value of the negative pressure state should be selected according to the specific temperature, boiling point and volatility of the composition. Specifically, ammonia water is volatile and has a low boiling point (38°C), and the negative pressure state can be used slightly or not; MMA monomer is volatile and has a medium boiling point (100°C), and the negative pressure state can be used moderately; photoinitiator, taking 2-hydroxy-2-methylpropiophenone as an example, is volatile, medium-low boiling point (80°C), and negative pressure can also be used moderately; diisocyanate, slightly less volatile, high boiling point (220°C), then the negative pressure state can be used heavily to further reduce the boiling point and accelerate the vaporization degree. Of course, changes in temperature will also affect the negative pressure effect. The two are positively correlated and can be used in combination according to actual conditions.

[0065] In S3, the negative pressure state is 30 to 60 min at 25 to 50 °C in order to better form the MMA gaseous atmosphere. Since MMA (boiling point 100 °C) exists in the homogeneous solution of the container and is volatile, a moderate thermal environment can vaporize MMA, and the negative pressure can make it fill more inside the constant temperature box, thereby depositing on the surface of the modified substrate and dissolving it appropriately. In this way, the surface of the substrate changes from a hard solid state to a soft "colloidal state". Under the action of their own gravity, the nanoparticles can partially enter the soft thin layer on the surface of the substrate at this time, that is, the anti-reflection layer is embedded in the surface of the substrate as a whole, and the spatial relationship between the two changes from point contact to surface contact, which significantly increases the mutual contact area and improves the bonding strength between the anti-reflection layer and the substrate surface. Please refer to Figure 3 After completing step S3, the nanoparticles partially enter the soft thin layer on the surface of the substrate under the action of their own gravity.

[0066] In S4, the negative pressure state is 30 to 60 min at 25 to 50 °C in order to better form a diisocyanate gas atmosphere. Since diisocyanate is also volatile, a moderate thermal environment combined with deep negative pressure can cause it to vaporize quickly and fill the interior of the constant temperature box, thereby infiltrating the nanoparticles and entering the embedded area of ​​the bottom and the substrate surface along its curved surface. Since the nanoparticles are obtained by the sol-gel process, the surface naturally contains abundant hydroxyl functional groups, and the substrate is mainly formed by copolymerization of hydroxyl-containing unsaturated monomers and MMA, so its surface and embedded concave surface contain a large number of hydroxyl groups. When encountering diisocyanate, addition reaction will occur quickly. Since the catalyst in the substrate has been dissolved by MMA in S3, even if the surface is dried before this step, the catalyst near the embedded surface will inevitably remain in a certain amount and activity, which will further accelerate the above reaction and can be quickly realized at room temperature. In this way, dense chemical bonding can be formed between the contact interface of the nanoparticles and the embedded concave surface of the substrate, improving the connection reliability between the two. Please refer to Figure 3 After completing step S4, dense chemical bonding is formed between the contact interface of the nanoparticles and the concave surface embedded in the substrate.

[0067] In S5, the negative pressure state is 30 to 60 min at 25 to 50 °C to form a better MMA gas atmosphere again, and the MMA is deposited on the surface of the modified matrix for appropriate surface dissolution. With its excellent wettability, it flows into and fills the gaps of the embedded interface. Since the homogeneous solution also includes a photoinitiator, it will enter a certain depth as the MMA moderately dissolves the surface of the matrix. Please refer to Figure 3 After completing step S5, the contact interface between the nanoparticles and the embedded concave surface of the substrate is filled with a solution composed of MMA and a photoinitiator.

[0068] Subsequently, the ultraviolet light source in the constant temperature box is turned on for irradiation treatment, which can cause the MMA monomers that enter the embedded gaps to undergo polymerization reaction, so that solid filling is formed between the nanoparticles and the surface of the substrate, eliminating the interfacial air, further increasing the bonding ability, and finally obtaining a robust modified substrate with surface-deposited nanoparticles, that is, an anti-reflective PMMA optical material. It is further explained that for the convenience of the operation process, the constant temperature box can simultaneously have the basic functions of heating and blowing, as well as the auxiliary functions of vacuuming (pressure relief) and ultraviolet light source. In this way, there is no need to use a vacuum oven that provides vacuuming (pressure relief) and a special curing box that provides ultraviolet irradiation, which shortens the process flow and improves the operating efficiency.

[0069] Further explanation, after S21 to S4 are completed, the blowing process is performed. The purpose of blowing after S21 is to remove the residual ammonia and fully dry the substrate surface at this time. The purpose of blowing after S3 is to remove the residual MMA monomer and photoinitiator and fully dry the substrate surface at this time. The purpose of blowing after S4 is to remove the residual diisocyanate and fully dry the substrate surface at this time.

[0070] The following are different embodiments for forming anti-reflection PMMA optical materials (see the manufacturing process for details). Figure 2 and Figure 3 ): Example 1 The steps include: S10. Providing a liquid matrix material, wherein the liquid matrix material comprises a prepolymerized liquid formed by bulk polymerization of MMA, a hydroxyl-containing unsaturated monomer, a catalyst, and a thermal initiator. Performing a polymerization reaction to form a solid matrix from the liquid matrix material; S20. Prepare a mixture of ethanol, tetraethyl silicate or tetraethyl titanate, and aqueous ammonia at room temperature (25°C), stir for 10 hours, seal with a light-shielding material, and let stand for 8 days to form a corresponding nanoparticle dispersion; S30. The solid matrix is ​​dried by hot air blast at 60°C for 5 min to remove trace moisture on the surface. Then, the corresponding nanoparticle dispersion is infiltrated and kept at 50°C until the surface is dry to form a preliminary modified matrix with nanoparticles deposited on the surface.

[0071] S40. Prepare a homogeneous solution consisting of MMA monomer and photoinitiator, and pour it into a container A of suitable size; take a certain amount of diisocyanate and pour it into a container B of suitable size; take a certain amount of ammonia water and pour it into a container C of suitable size. S41) Place container C and the preliminary modified matrix in a constant temperature box together, at 45 ℃, under negative pressure for 2 to 5 hours, release the pressure, and blow air for 30 minutes. S42) Open the constant temperature box, take out container C, put it into container A, at 25 to 50 ℃, under negative pressure for 30 to 60 minutes, release the pressure, and blow air for 30 minutes. S43) Open the constant temperature box, take out container A, put it into container B, at 25 to 50 ℃, under negative pressure for 30 to 60 minutes, release the pressure, and blow air for 30 minutes. S44) Open the constant temperature box, take out container B, put it back into container A, keep it at 25 ~ 50 ℃, keep it under negative pressure for 30 ~ 60 min, turn on the ultraviolet light source in the box, irradiate it for 30 min, and form surface deposited nanoparticles (such as Figure 1 The robust modified matrix (as shown) is an antireflective PMMA optical material.

[0072] In step S10, The viscosity of the prepolymer solution is 20 to 150 s for a 4-cup coating flow time at 25° C. In this embodiment, 20 s is specifically used.

[0073] The hydroxyl-containing unsaturated monomer is selected from at least one of hydroxypropyl methacrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxyethyl acrylate, 4-hydroxybutyl acrylate, 2,2-bis(allyloxymethyl)-1-butanol, methallyl alcohol, ethylene glycol monoallyl ether, 10-undecenol, 6-shogaol, curcumin, chlorogenic acid, caffeic acid, 4-coumaric acid, ferulic acid, sinapinic acid, 4-acetyl-2-allylphenol, 2-allylphenol, 4-hydroxystyrene, 4-isopropenylphenol, eugenol, 4-pentene-1-ol, 3-butene-1-ol, 1-butene-3-ol, 4-pentene-2-ol, cinnamyl alcohol, 3-allyloxy-1,2-propanediol, 3-methyl-2-butene-1-ol, 2-methyl-3-butene-2-ol, and 2-butene-1-ol. In this embodiment, hydroxypropyl methacrylate is specifically selected.

[0074] The catalyst is used to accelerate the reaction between the diisocyanate and the hydroxyl group, and is selected from at least one of dibutyltin dilaurate, dibutyltin diacetate, potassium neodecanoate, zinc neodecanoate, tetrabutyltin, dibutyldimethoxytin, monobutyltin triisooctanoate, trimethylamine, and triethylamine. In this embodiment, dibutyltin dilaurate is specifically selected.

[0075] The thermal initiator is used to initiate a polymerization reaction of the liquid matrix material to form a solid matrix, and is selected from at least one of BPO, AIBN, and ABVN. ABVN is specifically selected in this embodiment.

[0076] In one embodiment, in the liquid matrix material, the mass ratio of the prepolymer liquid, the hydroxyl-containing unsaturated monomer and the catalyst is (60-90): (5-20): (0.2-2), and the mass proportion of the thermal initiator in the liquid matrix material is ≤0.8%. In this embodiment, the mass ratio of the prepolymer liquid, hydroxypropyl methacrylate and dibutyltin dilaurate is specifically 60:5:0.2.

[0077] In one embodiment, the process of the polymerization reaction forms a plate with a thickness of less than or equal to 10 mm, specifically a water bath at 35 to 65°C for 2 to 12 hours, and a forced air bath at 105 to 135°C for 1 to 8 hours. When the thickness exceeds 10 mm, the specific water bath or air bath time should be adaptively extended according to actual conditions.

[0078] In this embodiment, the thickness is 8 mm, and the polymerization process is specifically 10 h in a water bath at 45 °C, and then 100 °C / 2 h, 120 °C / 3 h, and 135 °C / 2 h in a continuous blast air bath. Then turn off the heating power, cool naturally to less than 60 °C, open the oven, and take out for use.

[0079] Optionally, in step S20, In the mixture of ethanol, tetraethyl silicate or tetraethyl titanate, and ammonia water, the mass ratio of the ethanol, the tetraethyl silicate or tetraethyl titanate, and the ammonia water is (80-100): (5-15): (5-10). In this embodiment, the mass ratio of ethanol, tetraethyl silicate, and ammonia water is specifically 80:5:5.

[0080] In step S40, In the homogeneous solution composed of MMA monomer and photoinitiator, the mass ratio of MMA monomer to photoinitiator is 100:(0.2 ~ 2). In this embodiment, the mass ratio of MMA monomer to photoinitiator is specifically 100:0.2.

[0081] The photoinitiator is used to achieve polymerization reaction of MMA monomer under ultraviolet light, and is selected from 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl propiophenone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, and diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide. In this embodiment, 2-hydroxy-2-methyl propiophenone is specifically selected.

[0082] The diisocyanate includes at least one of p-phenylene diisocyanate, m-phenylene diisocyanate, 1,3-phenylene diisocyanate, toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, cyclohexane-1,4-diisocyanate, hexamethylene diisocyanate, toluene 2,5-diisocyanate, 2,2'-methylene diphenyl diisocyanate, trans-1,4-cyclohexane diisocyanate, isophorone diisocyanate, trimethyl hexamethylene diisocyanate, dicyclohexyl methane 4,4'-diisocyanate, 1,4-butyl diisocyanate, and 1,5-naphthalene diisocyanate. In this embodiment, 1,4-butyl diisocyanate is specifically selected.

[0083] Example 2 Compared with Example 1, the difference is: In step S10, The viscosity of the prepolymer solution is 150 s in this embodiment.

[0084] The hydroxyl-containing unsaturated monomer is specifically selected from ethylene glycol monoallyl ether in this embodiment.

[0085] The catalyst used in this embodiment is zinc neodecanoate.

[0086] The thermal initiator is AIBN.

[0087] In the liquid matrix material of this embodiment, the mass ratio of the prepolymer liquid, hydroxypropyl methacrylate and dibutyltin dilaurate is 90:20:2.

[0088] In step S20, The mixture of ethanol, tetraethyl silicate or tetraethyl titanate, and ammonia water, in this embodiment, the mass ratio of ethanol, tetraethyl titanate, and ammonia water is specifically 100:15:10.

[0089] In step S40, The configuration is a homogeneous solution composed of MMA monomer and photoinitiator. In this embodiment, the mass ratio of MMA monomer to photoinitiator is specifically 100:2.

[0090] The photoinitiator specifically uses 1-hydroxycyclohexyl phenyl ketone in this embodiment.

[0091] The diisocyanate in this embodiment specifically uses hexamethylene diisocyanate.

[0092] Everything else remains unchanged.

[0093] Example 3 Compared with Example 1, the difference is: In step S10, The viscosity of the prepolymer solution is 60 s in this embodiment.

[0094] The hydroxyl-containing unsaturated monomer is specifically selected from 3-allyloxy-1,2-propylene glycol in this embodiment.

[0095] The catalyst in this embodiment specifically uses triethylamine.

[0096] The thermal initiator is BPO.

[0097] In the liquid matrix material of this embodiment, the mass ratio of the prepolymer liquid, hydroxypropyl methacrylate and dibutyltin dilaurate is 75:12:1.2.

[0098] In step S20, The mixture of ethanol, tetraethyl silicate or tetraethyl titanate, and ammonia water, in this embodiment, the mass ratio of ethanol, tetraethyl silicate, and ammonia water is specifically 90:12:8.

[0099] In step S40, The configuration is a homogeneous solution composed of MMA monomer and photoinitiator. In this embodiment, the mass ratio of MMA monomer to photoinitiator is specifically 100:1.2.

[0100] The photoinitiator in this embodiment specifically uses 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone.

[0101] The diisocyanate in this embodiment is specifically para-phenylene diisocyanate.

[0102] Everything else remains unchanged.

[0103] Control group 1 The process is consistent with the existing manufacturing technology of ordinary PMMA materials, and the specific process will not be described in detail.

[0104] Control group 2 Compared with the control group 1, the only difference is the implementation of step S30. Specifically, the solid matrix (here specifically the material in the control group 1) is subjected to hot air drying at 60 ° C for 5 min to remove trace moisture on the surface. Then, the corresponding nano-silicon dioxide particle dispersion is infiltrated and kept at 50 ° C until the surface is dry, forming a modified matrix with nanoparticles deposited on the surface.

[0105] The performance of the anti-reflection PMMA optical materials manufactured in Examples 1 to 3 and Control Groups 1 to 2 was evaluated below. The specific test process is as follows: The shape, size and number of the test specimens used in Examples 1 to 3 and Control Groups 1 to 2 meet the standard requirements of the corresponding tests, and the results are averaged.

[0106] With reference to the requirements and methods in relevant standards such as GB / T 7134-2008 Cast industrial plexiglass sheets, GB / T 40911.3-2021 Plastic products - Types, dimensions and characteristics of polymethyl methacrylate sheets - Part 3: Continuously cast sheets, and GB / T 2411-2008 Plastics and hard rubber - Determination of indentation hardness (Shore hardness) using a hardness tester, the above-mentioned different basic physical properties were tested and characterized. Furthermore, with reference to the requirements and methods in ASTM D3359-08 Standard Test Methods for Measuring Adhesion by Tape Test, the adhesion was evaluated (between the anti-reflection layer and the substrate), and the results are shown in Table 1.

[0107] Table 1. Basic physical properties statistics

[0108] Note: aThe impact strength is the unnotched impact strength of a simply supported beam.

[0109] The results show that compared with control groups 1-2, embodiments 1-3 show good consistency in tensile strength, tensile elastic modulus, impact strength, tensile fracture strain, bending strength, bending elastic modulus, impact strength, hardness, and load deformation temperature. In addition, the present application conducted a stability analysis on the tensile strength, tensile elastic modulus, bending strength, and bending elastic modulus in the data, and the coefficient of dispersion was less than 2%, which further illustrates that the data fluctuates less. Therefore, compared with the ordinary PMMA substrate without any treatment, the embodiments in the present application have no statistically significant changes in physical and mechanical properties, that is, it is believed that the performance of the two has good consistency. In addition, the adhesion evaluation results of embodiments 1-3: there is no peeling on the edge of the grid, and the edge of the cut is completely smooth, belonging to the highest level 5B. However, compared with the sample in comparison 2, simulating the prior art, only the anti-reflection layer is implemented on the surface of the substrate, and no subsequent improvement measures are taken. The adhesion evaluation results: the peeling area of ​​the edge of the cut and the intersection is greater than 5% and less than 15%, and the grade is 3B, indicating that the technical solution in the present application can effectively improve the adhesion between the anti-reflection layer and the substrate.

[0110] Since there are great differences in the surface chemical environments between Examples 1 to 3 and Control Groups 1 to 2 in this application, especially the anti-reflection layers formed in Examples 1 to 3 and Control Group 2 are all realized by sol-gel process, and naturally have abundant hydroxyl groups and show hydrophilicity. Therefore, this application also conducted a static water contact angle test to further understand and grasp the differences. The results ( Figure 4 ) shows that the static water contact angles are 4.39° (Example 1), 4.97° (Example 2), 3.58° (Example 3), 67.50° (Control Group 1) and 2.46° (Control Group 2), respectively, indicating that the technical solution in the present application can achieve an extremely ideal hydrophilic effect compared to the ordinary PMMA sheet without any treatment (i.e., 67.50°). It should be emphasized that the static water contact angles of Examples 1 to 3 and Control Group 2 are all less than 5°, showing excellent super-hydrophilic properties. In order to clearly show the hydrophilic ability of the anti-reflection layer, the present application also performs dynamic video recording on the test process of Example 3, by capturing the freeze-frame images at different time points ( Figure 5 ), clearly demonstrating its ideal hydrophilic self-cleaning function. At the same time, the surface resistance of each group of materials was tested, which was greater than 10 compared with ordinary PMMA. 12 Ω insulation surface, the rest of the groups are 10 8 The antistatic surface of Ω indicates that it has good antistatic performance and is expected to further expand its scope of application.

[0111] The above control groups 1 to 2 and examples 1 to 3 were characterized by UV-Vis spectroscopy in a wavelength range of 200 to 1100 nm, wherein the transmittance test in the visible region was based on GB / T 7134-2008 Casting Industrial Organic Glass Sheet, and the transmittance data at a wavelength of 420 nm were used. The specific results are shown in Tables 1 and Figure 6 As shown, for Examples 1 to 3 and Control Group 2, when light enters the substrate from the outside, it first passes through the anti-reflection layer. Since the size of the nanoparticles (less than 100 nm) is much smaller than the starting point of the visible light band (i.e., 380 nm), the visible light wave will be effectively diffracted and pass through the anti-reflection layer almost intact, thereby not affecting the light transmittance of the visible light band. In addition, the presence of nanoparticles will further weaken the reflection effect when the light directly contacts the smooth surface of PMMA, that is, change from mirror reflection to diffuse reflection, eliminate the visual perception of glare, and part of the diffusely reflected light will be refracted by the curved surface of the nanoparticles and enter the substrate again, effectively improving the light transmittance of the substrate where the anti-reflection layer is located. This can be seen from Figure 6 This is well confirmed by the results: the transmittance of Examples 1 to 3 and Control Group 2 in the visible light band (380 to 780 nm) is greater than that of Control Group 1.

[0112] In addition, field emission scanning electron microscopy ( Figure 7 ) and atomic force microscopy characterization ( Figure 8 ), indicating that by adopting the technical solution in this application, an anti-reflection layer in which silicon dioxide nanoparticles (size range is 30 ~ 100 nm) are tightly arranged in the form of an array is formed on the surface of the substrate, with an average roughness of only 9.88nm, which is a two-dimensional planar structure with extremely high flatness.

[0113] The present application also provides an anti-reflection PMMA optical material, which is manufactured using the method for manufacturing the anti-reflection PMMA optical material described in the above embodiment.

[0114] The present application relates to an anti-reflection PMMA optical material and a manufacturing method thereof, the method comprising: infiltrating a dispersion of nanoparticles having a second functional group on the surface of a PMMA substrate having a first functional group on the surface; placing the modified PMMA substrate in a constant temperature box, controlling the temperature environment and negative pressure conditions, sequentially providing an ammonia atmosphere, a gas atmosphere composed of an MMA monomer and a photoinitiator, a gas atmosphere of a chemical substance for chemically bonding with the first functional group and the second functional group, and a gas atmosphere composed of an MMA monomer and a photoinitiator, and finally performing irradiation treatment to polymerize the MMA monomer to obtain an anti-reflection PMMA optical material. The technical solution of the present application, by providing different gas atmospheres and providing different gas atmospheres in sequence, can form chemical bonding and surface contact between the nanoparticles and the PMMA substrate, thereby improving the reliability of the anti-reflection layer, which is not only low in cost, but also has excellent mechanical properties and is durable.

[0115] The above embodiments are merely illustrative of the principles and effects of the present application and are not intended to limit the present application. Anyone familiar with the technology may modify or change the above embodiments without violating the spirit and scope of the present application. Therefore, all equivalent modifications or changes made by a person of ordinary skill in the art without departing from the spirit and technical ideas disclosed in the present application shall still be covered by the claims of the present application.

Claims

1. An anti-reflection PMMA optical material, characterized in that: The invention comprises a PMMA substrate and an anti-reflection layer formed on at least a part of the surface of the PMMA substrate, wherein the anti-reflection layer is composed of nanoparticles, chemical bonding is formed between the nanoparticles and the PMMA substrate, and at least a part of the nanoparticles is embedded in the surface of the PMMA substrate to form surface contact.

2. A method for manufacturing an anti-reflective PMMA optical material, characterized in that: The following steps are involved: S1, providing a PMMA substrate having a first functional group on the surface, and providing a dispersion of nanoparticles having a second functional group on the surface; S2, infiltrating the dispersion of the nanoparticles on at least a portion of the surface of the PMMA substrate, and drying, to obtain a first modified substrate; S3, placing the first modified substrate and a container containing a homogeneous solution composed of MMA monomer and photoinitiator in a constant temperature box, controlling the ambient temperature and negative pressure conditions, so that the MMA monomer and the photoinitiator are vaporized and deposited on the surface of the first modified substrate, dissolving and softening the surface of the first modified substrate, so that the nanoparticles are embedded in the surface of the first modified substrate to form surface contact, and obtaining a second modified substrate; S4, placing the second modified matrix and a container containing a chemical substance for chemically bonding with the first functional group and the second functional group in a constant temperature box, controlling the ambient temperature and negative pressure conditions, and vaporizing the chemical substance to infiltrate the surface of the nanoparticle and enter the surface contact area along the curved surface of the nanoparticle, forming a chemical bond between the nanoparticle and the second modified matrix in the surface contact area, and obtaining a third modified matrix; S5, placing the third modified substrate and a container containing a homogeneous solution composed of MMA monomer and photoinitiator in a constant temperature box, controlling the ambient temperature and negative pressure conditions, so that the MMA monomer and the photoinitiator are vaporized and deposited on the surface of the third modified substrate, dissolving and softening the surface of the third modified substrate and filling the surface contact area; S6, performing irradiation treatment to cause the MMA monomer to undergo a polymerization reaction, thereby obtaining an anti-reflective PMMA optical material.

3. The method according to claim 2, characterized in that The method of providing a PMMA substrate having a first functional group on its surface comprises: Providing a liquid matrix material, the liquid matrix material comprising a prepolymerized liquid formed by bulk polymerization of MMA, an unsaturated monomer containing the first functional group, the chemically bonded reaction catalyst and a thermal initiator; A polymerization reaction is carried out to make the liquid matrix material form a solid matrix, thereby obtaining a PMMA matrix having a first functional group on the surface.

4. The method according to claim 3, characterized in that In the liquid matrix material, the mass ratio of the prepolymer liquid, the unsaturated monomer containing the first functional group, and the chemically bonded reaction catalyst is (60 ~ 90): (5 ~ 20): (0.2 ~ 2), and the mass proportion of the thermal initiator in the liquid matrix material is ≤0.8%.

5. The method according to claim 3, characterized in that: The first functional group and the second functional group are both hydroxyl groups, and the chemical substance is diisocyanate; The first functional group is a primary amino group or a secondary amino group, the second functional group is a hydroxyl group, and the chemical substance is a first silane coupling agent; The first functional group is an epoxy group, the second functional group is a hydroxyl group, and the chemical substance is a second silane coupling agent.

6. The method according to claim 2, characterized in that The particle size of the nanoparticles is less than 380 nm, and the types of the nanoparticles include at least one of silicon dioxide and titanium dioxide.

7. The method according to claim 6, characterized in that The second functional group is a hydroxyl group, and the method of providing a dispersion of nanoparticles having the second functional group on the surface comprises: Prepare a mixture consisting of ethanol, tetraethyl silicate or tetraethyl titanate, and aqueous ammonia; After stirring for a certain period of time, the mixture is sealed with a light-shielding material and allowed to stand for aging to form a dispersion of nanoparticles having a second functional group on the surface.

8. The method according to claim 7, characterized in that Before S3, it also includes: The first modified substrate and a container containing ammonia water are placed in a constant temperature box, and the ambient temperature and negative pressure conditions are controlled to vaporize the ammonia water to obtain ammonia gas, which has a hardening effect on the anti-reflection layer composed of the nanoparticles.

9. The method according to any one of claims 2 to 8, characterized in that Include at least one of the following: In S3, the negative pressure state lasts for 30 to 60 minutes at 25 to 50 °C, and the product is dried by air blast after the pressure is released; In S4, the negative pressure state lasts for 30 to 60 minutes at 25 to 50 °C, and the product is dried by air blast after the pressure is released; In S5, the negative pressure state lasts for 30 to 60 min at 25 to 50 °C.

10. An anti-reflection PMMA optical material, characterized in that: The anti-reflection PMMA optical material is manufactured by the manufacturing method according to any one of claims 1 to 9.